Surveys in Combinatorics 2009 2009
DOI: 10.1017/cbo9781107325975.006
|View full text |Cite
|
Sign up to set email alerts
|

Extremal graph packing problems: Ore-type versus Dirac-type

Abstract: We discuss recent progress and unsolved problems concerning extremal graph packing, emphasizing connections between Dirac-type and Ore-type problems. Extra attention is paid to coloring, and especially equitable coloring, of graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 72 publications
2
22
0
Order By: Relevance
“…Theorem 1 improved previous bounds by Alon and Yuster [1], who showed that δ(H, n) ≤ (1 − 1/χ(H))n + o(n), and by Komlós, Sárközy and Szemerédi [11], who replaced the o(n)-term by a constant depending only on H. Further related results are discussed in the surveys [7,8,12,15,21].…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Theorem 1 improved previous bounds by Alon and Yuster [1], who showed that δ(H, n) ≤ (1 − 1/χ(H))n + o(n), and by Komlós, Sárközy and Szemerédi [11], who replaced the o(n)-term by a constant depending only on H. Further related results are discussed in the surveys [7,8,12,15,21].…”
Section: Introductionsupporting
confidence: 77%
“…for the Pósa-Seymour conjecture which states that every graph G on n vertices with δ(G) ≥ r r+1 n contains the rth power of a Hamilton cycle. [7] contains a discussion of other Ore-type results.…”
Section: 5mentioning
confidence: 99%
“…His theorem was generalized by Ore [24]: Assume that n ≥ 3, G is a graph of order n and for every xy ∈ E(G) we have deg(x) + deg(y) ≥ n. Then G has a Hamilton cycle. This result motivates the notion of the Ore-degree of an edge [17,21]: the Ore-degree of xy is the sum θ(x, y) = deg(x) + deg(y) Claim 3.3. Assume that H is a graph with θ(H) = 4.…”
Section: Introductionmentioning
confidence: 76%
“…The main open conjecture on the subject is the one of Bollobás and Eldridge [3] asserting that if (∆(G) + 1)(∆(H) + 1) ≤ n + 1 then G and H pack. Sauer and Spencer ( [9], see also Catlin's paper [4]) proved that this is the case if 2∆(G)∆(H) < n. For a survey of packing results including many extensions, variants and relevant references, see [7].…”
Section: Discussionmentioning
confidence: 99%